PENGARUH ASIMETRI INFORMASI, STRUKTUR KEPEMILIKAN MANAJERIAL, UKURAN PERUSAHAAN, DAN PROFITABILITAS TERHADAP MANAJEMEN LABA PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI - RIZKI AGUSTIAN, TAKDIR (Jurnal Akuntansi AKUNESA, 2016)
This study describes the effect of information asymmetry on earnings management, to determine the effect of managerial ownership structure on earnings management, to determine the effect of firm size on earnings management, and to determine the effect of profitability on earnings management of the banking companies listed in Indonesian Stock Exchange. The data used in this study is secondary data. The data is taken from the financial statements of companies listed in Indonesia Stock Exchange in 2010-2014. Sources of data obtained from www.idx.co.id. The population in this study are all companies in the banking sector, which is listed on the Indonesian Stock Exchange (IDX) in the range of 2010-2014 as many as 37 companies. The sample selection sampling method based on multiple criteria objectives. Based on these criteria obtained a sample of 13 companies. Figures in the observations used in this study is 5 years in a row so that the number of observations in this study were as many as 65 sample. The results showed that on partial information asymmetry, managerial ownership structure, and firm size has not been influence earnings management. While profitability influence significant earnings management of the banking companies listed in Indonesian Stock Exchange.